Criminal and Civil Responsibility of Hospital for Negligence of Nurses Who Inject Wrong Medicine - Dewangga, Ridho Cahya; Parikesit, Kiagus Handrian; Sapsudin, Asep (Research Horizon, 2025)
Medical negligence, especially nursing errors in administering drugs, can have serious impacts on patients and give rise to legal liability. This research aims to analyze the forms of criminal and civil liability of hospitals for negligence committed by nurses. Using a qualitative approach, this research collected data through in-depth interviews with health legal experts, medical practitioners, and related legal documentation. The research results show that nurse negligence can be subject to criminal sanctions in accordance with the Criminal Code if it causes injury or death to a patient. On the other hand, hospitals as institutions are civilly responsible based on the doctrine of vicarious liability, where hospitals can be asked for compensation for mistakes made by medical personnel. Determination of liability is influenced by various factors, including error rates, compliance with standard operating procedures, and internal hospital policies. This research makes an important contribution to understanding the legal dimensions of medical negligence and offers recommendations for strengthening regulations and safer medical practices.